Research and development of degree distribution in the rateless code - Yue QIAO; Yusun FU; Muyun YUAN; Jinhui TANG (Dianxin kexue)
As a kind of deletion coding technology, the rateless code reduces feedback retransmission and has the characteristics of flexible bit rate and simple compilation code, which has broad application prospects in many fields.As the basis of rateless code design, degree distribution has a crucial impact on the performance of the rateless code With the wide application of the rateless code, the design of degree distribution also needs to change with changes in scenarios and needs.Firstly, the development and application of the rateless code were discussed.Starting with several classical rateless codes and degree distributions, the current research and development of the degree distribution were summarized and analyzed from three perspectives of application scenarios, optimization targets and existing optimization methods.Finally, the development and application trend of rateless codes and degree distribution were discussed.